Ecological preferences of the Swiss pine (Pinus cembra L.) forests in the Gorgany Nature Reserve - Kuznetsov, R. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2023)
Swiss pine (Pinus cembra L.) is a montane Carpathian (Alpine-Carpathian) species. The modern distribution of the Swiss pine is disjunct, the two isolated areas are located in western and central Europe (Alps) and the middle and high mountains of the Carpathians. The largest areas of Swiss pine in Ukraine are preserved in the Gorgany region at the altitude of 1250‒1450 m above sea level, where it forms the upper forest line. In the Gorgany Nature Reserve, P. cembra grows in the altitude range from 1070 to 1475 m ASL. The lower boundary, in the form of individual trees, descends to 1000 m ASL, and the upper boundary rises to 1585 m ASL. To define the ecological preferences of the Swiss pine, a series of route surveys were conducted and research sites (permanent forest monitoring plots, stationary research profiles, and stationary areas for the counting of natural forest regeneration) were established. The study of the plant communities with P. cembra on the southwestern slopes of the Dzhurdzhi tract showed the dependence of the forest species composition on the altitude above sea level. The forest stands quantitative composition and productivity are also significantly influenced by slope exposure. The proportion of P. cembra in the forests on steep slopes (30‒55°) of west and north-west exposure is relatively high (from 17.1% to 49.0%). Under other conditions, the proportion of P. cembra in the stand composition gradually decreases. Swiss pine is almost completely absent on the slopes of eastern and northern exposures except for rare single trees in Pinus mugo Turra scrub on northern slopes. The forests with P. cembra are typical of sunny slopes where the available sum of active temperatures ranges between 1000° and 1400° and the average ambient temperatures from -12.2°С to +16°С. The optimal environmental conditions for the relict species P. cembra in the Dovbushanski Gorgany region are on the western slopes with a steepness of 17‒55° and southwestern and northwestern slopes with a steepness of 35°‒42°. In terms of soil fertility, oligotrophic edaphotopes with moderate moisture are optimal for the growth of Swiss pine.